THE FACTORS INFLUENCING THE SUCCESS OF BOUTIQUE HOTELS IN KLANG VALLEY, MALAYSIA - Ab Majid, Rohayu; Said, Rosli; Omar, Mohd Don; Wahid, Nurdiana; Rosman, Siti Hasniza (PLANNING MALAYSIA, 2024)
Boutique hotels, despite not matching the service level of 5-star counterparts, remain a flourishing presence in the hospitality industry, drawing a substantial influx of visitors. This study is dedicated to dissecting the contributory impact factors driving the triumph of boutique hotels in Malaysia. Delving into seven primary dimensions, these are further elaborated into a comprehensive framework of 28 sub-factors. Collated through a 210-strong questionnaire survey, the data collection was centred on patrons of boutique hotels situated in Malaysia's Klang Valley region. Employing inferential analysis techniques, the research probes the significance of these factors in shaping the fortunes of boutique hotels in the Malaysian context. The dataset underwent Chi-Square analysis to ascertain the noteworthy significance attached to each sub-factor. Notably, findings underscore that among the 28 scrutinised sub-factors, a notable set of 17 sub-factors establish a substantial correlation with visitor preferences, exerting a pivotal role in the overarching triumph of boutique hotels within Malaysia.